The investigation of care burden and coping style in caregivers of spinal cord injury patients - Hai-Ping Ma; Hui-Juan Lu; Xiao-Yun Xiong; Jian-Ying Yao; Zhen Yang (Elsevier, 2014)
Purpose: The level of care burden experienced by caregivers of patients with spinal cord injury and their coping style were evaluated in order to identify ways to improve their capacity to respond and reduce the care burden. Methods: A convenience sampling method was used to select 150 spinal cord injury patients who were discharged from the Second and the Third Affiliated Hospital of Nanchang University and their primary caregivers. The Chinese version of the Zarit Caregiver Burden Interview and the Simplified Coping Style Questionnaire were distributed to assess caregiver burden and coping strategies. Results: The care burden score of the caregivers of patients with spinal cord injury was 52.91 ± 11.56 points. Eighty-eight percent of caregivers reported moderate or severe care burden levels. The largest proportion of caregivers were female spouses, who were less likely to use an active coping strategy. A negative coping strategy was more frequently used by caregivers compared to healthy adults, and was positively correlated with burden of care. In contrast, a negative correlation was found between the care burden and an active coping style. Conclusion: Primary caregivers of spinal cord injury patients report a heavy burden of care. As active coping strategies are more beneficial, medical care providers should encourage caregivers to make more use of these coping styles to promote physical and mental health for themselves, their patients and their family, as well as to improve the quality of care provided.